How to teach writing - Harmer, Jeremy (Longman, 2004)
The book offers a practical guide to the theory of writing and covers a range of approaches to the teaching of writing. It also delivers an uncomplicated analysis of the nature of writing, particularly in terms of process, product, and genre. Descriptions of a broad range of writing tasks enable teachers to select those that will be most effective in developing students' writing skills